FRI0621 Hospital admissions and readmissions in patients with rheumatoid arthritis. associated factors and direct health-care costs in a third level university hospital. (12th June 2018) - Ruiz-Sará, J. E.; Lozano-Rivas, N.; Castillo Dayer, P.; García-Belando, C.; Paños-Iniesta, A.; Linares, L. F.; Bermudez, A.; Martínez-Angosto, F. A.; Martínez-Ferrín, J.; Moreno, M. J.; Castaño, M.; Mesa del Castillo, P.; et al.
Abstract : Background: In last years, the direct health-care costs derived from admissions and readmissions to Rheumatology departments of patients with Rheumatoid Arthritis (RA) have diminished. Presumably, the higher survival rate and the amount of comorbidities of these patients have derived in an increased of admissions and direct costs to other medical and surgical departments. Objectives: To describe the admission and readmission causes of all patients with RA admitted during 2015 and 2016 and to identify factors associated to readmission. Finally to estimate the costs derived from these events in the same period. Methods: All electronic medical reports were revised; demographic, medical and therapeutic data, as well as diagnosis at discharge were collected. A descriptive analysis followed by a logistic regression analysis were done to identify readmission-associated variables. Financial analysis was done by calculating the price of the stay according to established in 2015-scale. Results: 240 admissions of 158 patients were found. Mean age 63, 8 years, 69% women and mean evolution of RA of 13, 1 years. At admission, 53% were on oral steroids and 45% with synthetic DMARD. Admissions were mainly distributed in Internal Medicine department (26%). Infections were the most frequent admission cause (33%), followed by cardiovascular events (20%) and oncological processes (13%). Forty-nine patients (31%) were readmitted, 47% due to infections. Age (OR/year 1.02 CI 95% 1.00–1.04), diabetes (OR 2.1 CI 95% 1.1–4.4) and chronic kidney disease (OR 3.3 CI 95% 1.0–10.2) were the associated risk factors. There were a total of 2172 days of stay with an estimated cost of 530420 euros and 783 days of stay due to readmissions with a total cost of 203218 euros. Departments which generated more costs either for admissions or readmissions were Oncology (65064 euros/19585 euros respectively) and Intensive Care (68011 euros/42651 respectively). Costs for admission and readmission in Rheumatology department were 5230 and 3175 euros respectively. Conclusions: Admission and readmission of patients with RA are mostly due to infections and cardiovascular causes. Estimated direct costs are higher for patients admitted to Intensive Care Unit or Oncology Disclosure of Interest: None declared